Analysis of Inventory Accounting Implementation Based on PSAK No. 14 at PD. Karya Cipta Mandiri - Muhammad Sodri; Badriah, Sopi; Uzliawati, Lia (Review of Accounting and Taxation, 2024)
Purpose - The objective of this research is to analyze the application of inventory accounting at PD. Karya Cipta Mandiri using PSAK No. 14 as a guideline. Design/methodology/approach – The research method employed in this research is a qualitative method with a descriptive approach. Data collection is conducted through two main methods, that is direct observation and interaction via interviews. Finding – The analysis results indicate that the company adopts the perpetual method for recording and the FIFO method for inventory valuation. Based on these findings, it is concluded that the implementation of inventory accounting at PD. Karya Cipta Mandiri is in accordance with the provisions of PSAK Number 14 regarding inventory. Originality – This study analyzes the implementation of inventory in trading companies from an accounting perspective. It evaluates how the company conducts inventory accounting and compares it with inventory accounting in PSAK No. 14, which serves as the guideline for corporate accounting practices.